2017
DOI: 10.1016/j.bbrc.2017.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 3 regulates chemokine expression in contracting C2C12 myotubes and in mouse skeletal muscle after eccentric exercise

Abstract: a b s t r a c tActivating transcription factor (ATF) 3 regulates chemokine expression in various cell types and tissues. Herein, we studied this regulation in contracting muscle cells in vitro, and in skeletal muscle after muscle-damaging exercise in vivo. C 2 C 12 myotubes with normal or low ATF3 levels (atf3_siRNA) were electrically stimulated (EPS). Also, ATF3-knockout (ATF3-KO) and control mice ran downhill until exhaustion, and muscles were analyzed post-exercise. EPS increased ATF3 levels in myotubes (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…49 Finally, a robust upregulation of Atf3 mRNA (8-fold) was observed following weightlifting (Figure 2D). Upregulation of Atf3 gene, which was induced by eccentric contractions, 50 has anti-inflammatory roles by inhibiting chemokine and cytokine expression. 51 These findings support that acute weightlifting elicits transcriptome responses as an early step in skeletal muscle adaptation to resistance exercise, laying a foundation for future dissection of molecular mechanisms underlying structural and functional adaptations to resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…49 Finally, a robust upregulation of Atf3 mRNA (8-fold) was observed following weightlifting (Figure 2D). Upregulation of Atf3 gene, which was induced by eccentric contractions, 50 has anti-inflammatory roles by inhibiting chemokine and cytokine expression. 51 These findings support that acute weightlifting elicits transcriptome responses as an early step in skeletal muscle adaptation to resistance exercise, laying a foundation for future dissection of molecular mechanisms underlying structural and functional adaptations to resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we wonder whether ATF3 could also regulate the transcription of a gene to participate in cerebral ischemia. Postexercise, ATF3‐knockout mice showed exacerbated mRNA levels of CCL2 and interleukin (IL)‐1β (Fernandez‐Verdejo et al., 2017 ), indicating the possible connection between ATF3 and CCL2. Furthermore, CCL2 is involved in the signaling pathways recruiting microglia after repetitive head impacts and may serve as a future therapeutic target in chronic traumatic encephalopathy (Cherry et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two main groups of cell types were used in the included studies: a. cell lines and b. biopsies from humans and mice ( Table S2 ). More specifically, 30 of the eligible studies used cell lines: 24 studies employed the C2C12 cell line [ 16 , 17 , 26 , 28 , 30 , 31 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], a mouse myoblast cell line; while one study used the L6 cell line [ 55 ], a rat myoblast cell line; one used primary human cells [ 13 ]; and one the H-2kb muscle cells (a mouse myoblast cell line) [ 56 ]. Of the remaining eligible studies, 12 used human skeletal muscle biopsies [ 18 , 19 , 20 , 21 , 23 , 24 , 25 , 29 , 50 , 57 , 58 , 59 , 60 ] from different sites, such as vastus lateralis, satellite cells, and rectus abdominis, obtained from healthy ( n = 64), lean ( n = 32), obese ( n = 20), and diabetic donors ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…The protocol used by Breton et al [ 24 ] was the only one where we detected linking both acute (30 min stimulation) and chronic (3 day stimulation) protocols to resistance training in vitro. Furthermore, three studies [ 39 , 52 , 60 ] identified their EPS model as “endurance training”, either establishing the optimal conditions for EPS to mimic endurance training in vitro (60 min, 11.5 V, 10 Hz) or using an already established protocol (240 min, 20 V, 1 Hz) that was previously proven to mimic endurance exercise in vitro [ 62 ].…”
Section: Resultsmentioning
confidence: 99%